2012
DOI: 10.2139/ssrn.2164322
|View full text |Cite
|
Sign up to set email alerts
|

Honest Grading, Grade Inflation and Reputation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The present analysis can be developed in several directions. A possible extension may evaluate the relationship between grade inflation and school reputation (see Ehlers and Schwager 2016) when students differ in social background. In this line, it would be necessary to modify the framework in a dynamic setting and to relax the assumption of perfect information about the school strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analysis can be developed in several directions. A possible extension may evaluate the relationship between grade inflation and school reputation (see Ehlers and Schwager 2016) when students differ in social background. In this line, it would be necessary to modify the framework in a dynamic setting and to relax the assumption of perfect information about the school strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus inflating schools mutually reinforce each other's practices. Ehlers and Schwager (2016) modify the analysis of Chan, Hao, and Suen (2007) by introducing a reputational element. They add a second cohort of graduates that arrives in the labour market when the first cohort has already revealed their true ability and therefore the school's grading policy.…”
Section: Related Literaturementioning
confidence: 99%
“…Unfortunately, it is sufficient to add a reputational cost to the model to show that, when employers learn that students' ability does not match with grades, they start to penalize students from those departments. Then, students will learn that inflating-grades departments are not able to place them on the labor market, starting to avoid them (Ehlers and Schwager, 2016).…”
Section: Soft Grading Policies: Comparing Different Perspectivesmentioning
confidence: 99%
“…On the other hand, some studies recommended solutions for grade inflation. These are separating student evaluations of teaching quality and teacher promotion, or controlling for student-teacher evaluations in the research on teacher quality; 2) Deepening teacher quality, teaching quality, curriculum design quality, and academic rigor, and assessment and evaluations; 3) Reports to Baker also indicated that the power to shift the effect of grade inflation is in the hands of policymakers, higher-order officials and politicians (Baker;2018;Ehlers & Schwager, 2012;Yorke;2004). Among the strong factors that underlie grade inflation, Baker's (2018) report tells us that student fee-paying for their education is the most one.…”
Section: Real and Nominal Grade Differences And The Applicability Of mentioning
confidence: 99%
“…As a result, they may spoil the quality of graduates in particular and the quality of education in general (Cruskey, Griffin and Ehlen, 2010). Grades lose their credibility because the percentage of learners who receive higher grades rises without any equivalent increase in student performance (Ehlers & Schwager, 2012). This is called grade inflation.…”
Section: Introductionmentioning
confidence: 99%